Sexual and reproductive health communication between parents and high school adolescents in Vientiane Prefecture, Lao PDR - Visany Vongsavanh; Vu Thi Hoang Lan; Vanphanom Sychareun (Taylor & Francis Group, 2020)
Background Adolescent health has become a priority on the global health agenda. Parent-adolescent communication regarding sexual and reproductive health (SRH) issues can help to reduce adolescent risk-taking sexual behaviours. Objective This study was to describe the situation of SRH communication, and to determine the factors associated with SRH communication between high school students and their parents in Vientiane Capital prefecture, Lao PDR. Methods A multistage sampling technique was applied. A self-administered questionnaire was implemented among a sample of 384 high school students aged 14-17 in Vientiane. SRH communication in this study was recorded as the frequency with which adolescents discussed with their parents at least four topics on SRH issues during a six-month period prior to the interview. Data were entered and analysed using Epi Data software version 6.0 and STATA software version 14.2. Results Slightly more than one-fifth of the students (21.3%) communicated with parents on SRH issues. The multivariate logistic regression model showed that being a male adolescent (AOR = 2.1; 95% CI 1.2 to 3.5), urban school locations (AOR = 0.2; 95% CI 0.1 to 0.5), a mature father (AOR = 1.7; 95% CI 1.0 to 2.9), positive attitudes towards general communication with parents (AOR = 2.2; 95% CI 1.1 to 4.2) and accessibility to multiple SRH information sources (AOR = 5.2; 95% CI 2.4 to 11.4) were significantly associated with adolescent-parent communication on SRH issues. Conclusion This study showed that student-parent communication on SRH issues was low, so policymakers should develop programs to improve SRH communication skills in all schools and encourage open discussion among family members, especially with respect to the participation of adolescent girls. The positive attitudes of students and multiple sources of SRH information were also important factors in improving SRH communication.